The ex-ante versus ex-post effect of public guarantees - Evren Damar; Reint E. Gropp; Adi Mordel (Bank of Canada, 2012)
In October 2006, Dominion Bond Rating Service (DBRS) introduced new ratings for banks that account for the potential of government support. The rating changes are not a reflection of any changes in the respective banks' credit fundamentals. We use this natural experiment to evaluate the consequences of bail out expectations for bank behavior using a difference in differences approach. The results suggest a striking difference between the effects of bail out probabilities during calm times (ex ante) versus during crisis times (ex post). During calm times, higher bail-out probabilities result in higher risk taking, consistent with the moral hazard view and much of the empirical literature. However, in crisis times, we find that banks with higher bail out probabilities tend to increase their risk taking less compared to banks that were ex ante unlikely to be bailed-out. Charter values are one part of the explanation: Supported banks may have a funding advantage relative to non-supported banks during the crisis. However, we cannot rule out that other factors also may be playing a role, including tighter supervision of supported banks in crisis times.
Keywords: G21; G28; G32; 330; Financial institutions; Financial system regulation and policies; Financial stability